Gut Microbiota and Sunitinib-Induced Diarrhea in Metastatic Renal Cell Carcinoma: A Pilot Study - Su Z (Dove Medical Press, 2021)
Zhimin Su,1,2 Linbin Lu,1 Fuyu Chen,3 Jianhui Chen,4 Xiong Chen1 1Department of Oncology, 900th Hospital of PLA, Fuzong Clinical Medical College of Fujian Medical University, Fuzhou, 350024, People’s Republic of China; 2Department of Medical Oncology, Xiamen Branch, Zhongshan Hospital, Fudan University, Xiamen, 361015, People’s Republic of China; 3Department of Substation Maintenance Center, State Grid Quanzhou Electric Power Supply Company, Quanzhou, 362000, People’s Republic of China; 4Department of Urology, Fujian Medical University Union Hospital, Fuzhou, 350024, People’s Republic of ChinaCorrespondence: Xiong ChenDepartment of Oncology, 900th Hospital of PLA, Fuzong Clinical Medical College of Fujian Medical University, 156 North Xierhuan Road, Fuzhou, 350024, People’s Republic of ChinaEmail cxiongzpc@fjmu.edu.cnIntroduction: Sunitinib-induced diarrhea seriously affects the prognosis of patients with metastatic renal cell carcinoma (mRCC) and reduces their quality of life. We aim to explore and find the relationship between sunitinib-induced diarrhea and gut microbiota.Methods: Feces were collected from 31 mRCC patients receiving sunitinib treatment. To characterize the feces gut microbiome profiles of patients, the V3-V4 region of 16S rRNA sequencing was carried out in this study.Results: Gut microbial diversity was decreased both in the severe diarrhea group and in the sunitinib-post group. The microbial composition with higher abundance of Bacteroides (mucus degrading bacteria) and lower abundance of Faecalibacterium, Oscillospira, Ruminococcaceae, Eubacterium and Coriobacteriaceae (butyrate-producing bacteria) were found in patients with diarrhea. Interestingly, the abundance of Actinobacteria was decreased in patients receiving sunitinib with severe diarrhea.Conclusion: This study reported an association between gut microbiota and sunitinib-induced diarrhea. Defects of the butyrate-producing bacteria and the increase in Bacteroides may be the physiological basis of sunitinib-induced diarrhea.Keywords: sunitinib-induced diarrhea, 16S rRNA sequencing, gut microbial diversity, butyrate-producing bacteria